2016
DOI: 10.1016/j.celrep.2016.09.026
|View full text |Cite
|
Sign up to set email alerts
|

PAXX Is an Accessory c-NHEJ Factor that Associates with Ku70 and Has Overlapping Functions with XLF

Abstract: In mammalian cells, classical non-homologous end joining (c-NHEJ) is critical for DNA double-strand break repair induced by ionizing radiation and during V(D)J recombination in developing B and T lymphocytes. Recently, PAXX was identified as a c-NHEJ core component. We report here that PAXX-deficient cells exhibit a cellular phenotype uncharacteristic of a deficiency in c-NHEJ core components. PAXX-deficient cells display normal sensitivity to radiomimetic drugs, are proficient in transient V(D)J recombination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
74
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 53 publications
10
74
2
Order By: Relevance
“…Competitions experiments showed that the X-KBM peptide (pXLF) competes in the μM range with the XLF protein and that the A-KBM peptide (pAPLF) does not displace XLF, supporting remote sites of interactions (Figure 2e and Supplementary Figure 3c, d). Also, the C-terminus of PAXX (pPAXX) does not compete with XLF binding, in agreement with previous studies that report an interaction between PAXX C-terminus and Ku70 subunit 22,23 (Supplementary Figure 3e). …”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Competitions experiments showed that the X-KBM peptide (pXLF) competes in the μM range with the XLF protein and that the A-KBM peptide (pAPLF) does not displace XLF, supporting remote sites of interactions (Figure 2e and Supplementary Figure 3c, d). Also, the C-terminus of PAXX (pPAXX) does not compete with XLF binding, in agreement with previous studies that report an interaction between PAXX C-terminus and Ku70 subunit 22,23 (Supplementary Figure 3e). …”
Section: Resultssupporting
confidence: 92%
“…Wild-type XLF onto the Ku-DNA complex showed a rapid k on (4.7 ± 1.7 10 5 M −1 s −1 ) followed by a rapid dissociation (k off = 0,09 ± 0,004s −1 ) and a corresponding Kd of 0.19 ± 0.07 μM (Figure 4a). This affinity is about 10 fold stronger than the one measured by ITC with a smaller DNA and may reflect additional interactions of XLF with DNA emerging from Ku ring as observed with PAXX 22 . LW and LE mutants showed a 2.3- and 5.1-fold weaker affinity than WT protein, respectively (Kd of 0.45 ± 0.26 μM for LW and Kd of 0.98 ± 0.15 μM for LE) Supplementary Figure 3h).…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…The C-terminus of PAXX (aa 199 -201) interacts with Ku, and similar to XLF mutants, PAXX mutants are more sensitive to ionizing radiation and DSB inducing agents ( Fig. 2) (64,66,67).…”
Section: The Ligase Complex Of Nhejmentioning
confidence: 99%
“…PAXX is recruited to DNAdsb and is a physical interactor of the Ku/DNAPK complex, notably through its interaction with Ku70. 11 Surprisingly, for a NHEJ factor, the deficiency of PAXX does not systematically result in an increased sensitivity to ionizing radiation (IR) and the results of the various DNA repair assays are highly controversial, depending on the experimental settings. [8][9][10][12][13][14][15] This suggested a possible functional complementation of PAXX deficiency in certain conditions.…”
mentioning
confidence: 99%